Reliability, Consistency and Temporal Stability of Alberta Infant Motor Scale in Serbian Infants - Milan Lackovic; Dejan Nikolic; Dejan Filimonovic; Ivana Petronic; Sladjana Mihajlovic; Zoran Golubovic; Polina Pavicevic; Dragana Cirovic (MDPI AG, 2020)
Our study aimed to analyze the reliability, consistency, and temporal stability of the Alberta Infant Motor Scale (AIMS) in Serbian infants. Additionally, we aimed to present a percentile distribution of AIMS in the tested population. The prospective study included 60 infants that were divided into three age groups: 0−3 months, 4−7 months, and 8−14 months. The Serbian version of AIMS was tested by two raters on two different occasions (test/retest) with a five day period between tests. The observed inter-rater reliability (intraclass correlation coefficient (ICC)) was more than 0.75 for all AIMS scores, except for standing (ICC 0.655 = moderate) in the age group of 4−7 months on retest between raters. The observed intra-rater reliability (ICC) was more than 0.75 for all AIMS scores except standing (ICC 0.655 = moderate) in the age group 4−7 months in test−retest for Rater One, and for sitting (ICC 0.671 = moderate) and standing (ICC 0.725 = moderate) in the age group between 0−3 months on test−retest for Rater Two. The Serbian version of AIMS was shown to have high consistency and high reliability with good to high temporal stability. Thus, it can be used in the evaluation of infants’ motor development in Serbia.